The attitudes of faculty members in the College of Media towards the use of electronic information sources - عبد الحسين مدهوش م.د.قادر (Thi Qar Arts Journal, 2025)
The research aims to understand the reality of faculty members’ use of electronic resources, the types they prefer, the purposes for which they use these resources, and the difficulties they face in using them. The research adopted a field method using description and analysis, where data was collected through a questionnaire consisting of five axes, each axis comprising five questions. The questionnaire was distributed to a sample of fifty faculty members, and all forms were retrieved. The research reached a set of conclusions, the most prominent of which are: the weak reliance of faculty members on electronic resources through the college library due to the unavailability of these resources, leading them to resort to other means to access them. Faculty members agreed that the reasons for choosing electronic resources include the ease of searching, the minimal effort required, and the ease of access. They heavily rely on electronic journals as primary sources for scientific research due to the presence of recent and diverse research and articles in all fields. The research proposed several recommendations, including holding workshops, seminars, and scientific lectures that focus on the importance of using electronic information sources, providing financial support to the library to enhance internet services, and the necessity of supporting the college library by allocating part of its budget to purchase subscriptions to academic databases and international electronic journals.